Preparation of a polyvinylidene fluoride tree-like nanofiber mat loaded with manganese dioxide for highly efficient lead adsorption. Issue 14 (23rd January 2017) - Li, Zongjie; Kang, Weimin; Wei, Na; Qiu, Jiuan; Sun, Cheng; Cheng, Bowen
Abstract : A novel polyvinylidene fluoride tree-like structure nanofiber mat loaded with manganese dioxide as a highly efficient lead adsorbent was fabricated. Abstract : A novel polyvinylidene fluoride/tetrabutylammonium chloride (PVDF/TBAC) tree-like nanofiber mat loaded with manganese dioxide (MnO2 ) as a highly efficient lead adsorbent was successfully fabricated. The adsorbent was prepared by in situ polymerization of pyrrole monomer on the surface of the PVDF/TBAC tree-like nanofiber mat, and subsequently reacted with KMnO4 solution to deposit MnO2 . The morphology and structure of the as-prepared adsorbent were measured by field emission scanning electron microscopy (FE-SEM) and the tree-like structures can be clearly seen from the FE-SEM images. Fourier transform infrared spectroscopy (FT-IR) results confirmed the presence of PPy and MnO2 layers on the surface of PVDF/TBAC tree-like nanofibers. Thermo-gravimetric analysis (TGA) results exhibited that MnO2 accounted for about 43.27% in the PVDF/TBAC–polypyrrole–MnO2 (PVDF/TBAC–PPy–MnO2 ) nanofiber mat. The kinetics of Pb 2+ adsorption was found to follow a pseudo-second-order rate model. The adsorption isotherms were fitted best with the Langmuir isotherm model. The thermodynamic analysis confirmed that the adsorption process was endothermic and spontaneous. The regeneration experiments showed that the obtained tree-like PVDF/TBAC–PPy–MnO2 nanofiber mat also exhibited high recyclable removal efficiency. XPS analysis showed that ion exchange was the main mechanism for Pb 2+ adsorption.